Islamic Boarding School and Community Empowerment - Sarwadi Sulisno; Azis Abdullah (Association for Scientific Computing Electrical and Engineering(ASCEE), 2019)
Islamic education has contributed since before independence. As a long journey requires a spirit that can guide and support to get to the point of success at any time. Mental entrepreneurship can provide the spirit of education to be able to disrupt itself in order to be able to exist with all the challenges of globalization in the digital era. Mental entrepreneurship is a skill that does not only make things from nothing and makes some things from some other things, but also the ability to see and predict the challenges of current and futuristic challenges, then do disruption either by reshape old one -Create a new one to the existing pattern. Entrepreneurship ability will be formed after soft skill entrepreneurship abilities are possessed by students. Until the peak of entrepreneurship of Islamic edication was to view disruption as an opportunity to lead to a new Islamic education.